2005
DOI: 10.1111/j.1365-2184.2005.00328.x
|View full text |Cite
|
Sign up to set email alerts
|

CD19 signalling improves the Epstein–Barr virus‐induced immortalization of human B cell

Abstract: Epstein-Barr virus (EBV) infection in vitro immortalizes primary B cells and generates B lymphoblastoid cell lines (LCLs). These EBV-LCLs have been used for several purposes in immunological and genetic studies, but some trials involving these transformations fail for unknown reasons, and several EBV-LCLs do not grow in normal culture. In this study, we improved the immortalization method by CD19 and B-cell receptor (BCR) co-ligation. This method shortens the time required for the immortalization and generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…(2003) found that in the transformation efficiency of a group infected with tetradecanoyl phorbol acetate, the induced EBV was higher than that of their control group. Recently, Hur et al (2005) found that numbers of cell clumps and expression of CD38 in LCLs could be enhanced by CD19 ligation. Mello et al .…”
Section: Discussionmentioning
confidence: 99%
“…(2003) found that in the transformation efficiency of a group infected with tetradecanoyl phorbol acetate, the induced EBV was higher than that of their control group. Recently, Hur et al (2005) found that numbers of cell clumps and expression of CD38 in LCLs could be enhanced by CD19 ligation. Mello et al .…”
Section: Discussionmentioning
confidence: 99%
“…To ensure sufficient cell numbers for these experiments, we used EBVtransformed B cells as a model to study the expression of CD38 and iNOS, as well as the production of different pro-and antiinflammatory cytokines, including IL-1b, IL-2, IL-6, IL-8, TNF-a, IFN-g, IL-4, and IL-10. According to previous studies, EBV transformation of primary human B cells changes various cellular properties (23,24), such as the expression of the cell activation-associated Ag CD38 (25), and the expression of iNOS (26). Furthermore, B-LCLs have been described as expressing various cytokines with a high degree of heterogeneity (24,(27)(28)(29)(30)(31)(32).…”
Section: Inos-expressing B Lineage Cells Produce Pro-and Antiinflammamentioning
confidence: 99%
“…It could be postulated that, due to the attached CD19-conjugated magnetic beads on the B-cells, the positively-selected cells had less capability to undergo EBV transformation compared to negativelyselected counterparts. However, Hur et al (2005) reported that attachment of anti-CD19 polyclonal antibodies to B-cells during MACS-mediated positive selection increased expression of cytosolic (but not membranous) LMP-1 proteins that have a critical role in EBV transformation of B-cells. It is also possible the binding of CD19-beads may have induced conformational changes that disrupted the EBV ability to infect the cells via CD21, as both molecules are part of the B-cell receptor complex.…”
Section: Discussionmentioning
confidence: 99%
“…For example, CD19 and BCR co-ligation has been shown to boost EBV transformation and establishment of LCL (Hur et al 2005). Nevertheless, little is known about the effect of choice of method by which B-cells are isolated on these parameters.…”
Section: Introductionmentioning
confidence: 99%